Pendekatan Culturally Responsive Teaching (CRT) dalam Peningkatan Kemampuan Berpikir Kritis Siswa Kejuruan Kuliner - Luthfi Novela; Yunus Karyanto; Lailatul Firman Dyah Maulya; Dwi Apriliani (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to investigate the application of the Culturally Responsive Teaching (CRT) approach in enhancing learning outcomes and critical thinking skills of vocational high school students in the culinary department, specifically in the subject of Indonesian Cake and Pastry Production (PCKI) on the topic of Indonesian cake classification. The research employed a pre-experimental design with a one group pre-test post-test model, involving 33 students of class XI WU PB at SMKN 1 Buduran, East Java. Data were collected through essay tests and observation questionnaires, analyzed using percentage of learning mastery and critical thinking level qualification techniques. The results showed an increase in classical mastery from 45.4% in the pre-cycle to 60.6% in cycle I and 78.8% in cycle II. Critical thinking skills also improved, with the percentage of students in the "Very Critical" and "Critical" categories increasing by 9% and 6%, respectively, in cycle II. The CRT approach, which integrates local culture, has proven effective in creating meaningful learning, improving learning outcomes, and enhancing critical thinking skills. The PCKI subject is essential for culinary vocational students to prepare them as competent workers capable of preserving and promoting traditional Indonesian cakes in the culinary industry.